Political discourse and semiotics - Çanakpınar, Betül; Kalelioğlu, Murat; Günay, Veli Doğan (Chinese semiotic studies = Zhongguo fu hao xue yan jiu, 2024)
In recent years, semiotics has put “life” at the center of the subject of study. There is the desire to be successful in the lifestyle and the desire to convey the right knowledge to the recipient or the correct use of practices in life. A semiotic theory developed by Jacques Fontanille recently showed that strategy can also be used in semiotic analysis. So, the way of life that Fontanille talks about is not just strategy. The process we call “lifestyle” has an order from small to large: There are basic signs, texts, objects, actants, practices, action phases, strategies, and finally lifestyle. In this study, we question the function of strategy, but generally of productive pursuit, in the analysis of political discourses. In our study, we reveal the approach of semiotics to political discourses that concern the whole world and discuss whether they are valid in every society. We emphasize political semiotics, which is used to understand the general structure of political discourses, and show the general functioning of political discourses with Greimas’ Actantial Model. We conclude that politicians can influence target audiences by using various methods and discourse strategies.